Biomass Derived Heterogeneous and Homogeneous Catalysts - Martín, José María Encinar; Delgado, Sergio Nogales (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book, the performance of homogeneous and heterogeneous catalysts applied in biomass processing was assessed, paying special attention to the main advantages and challenges related to their use. Indeed, these challenges are opportunities to develop new research lines that could be fruitful in the near future. Thus, different studies are included, dealing with diverse subjects, with one main goal in common: the improvement of different aspects related to biomass processing through the use of catalysts.